Peningkatan Kinerja Badan Usaha Milik Nagari (BUMNAG) Melalui Pelatihan dan Pengembangan Sistem Informasi Akuntansi - Endrawati Endrawati; Ike Rahmadani; Riyan Ikhbal Sala; Zulvitri Zulvitri (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Nagari-owned enterprises (BUMNag) are a means to manage nagari assets into businesses that have economic value in increasing the nagari's original income. BUMNag is expected to be able to guarantee an increase in public services and the welfare of the nagari community. This program aims to improve the performance of BUMNag in financial management and business operations through the development of an accounting information system (SIA) and provide knowledge and skills to BUMNag managers regarding the SIA. This program is implemented through design, training, and mentoring as well as evaluation to see the success of the activity. The activity has produced a prototype of SIA development that can be applied by BUMNag and also increases the knowledge and skills of managers. In addition, the output of the activity is the SIA application training module